2016
DOI: 10.1177/0081246316646950
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for posttraumatic stress disorder: a review of the evidence base

Abstract: Given high rates of trauma exposure in South Africa, mental health practitioners often need to deliver interventions to trauma survivors. While there have been few local trauma intervention studies, there is an extensive international evidence base that provides a rich resource on which to draw. This article reviews evidence-based treatments for posttraumatic stress disorder and complex posttraumatic stress disorder. The current weight of evidence supports the use of trauma-focused cognitive behavioural therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…These variables are aggregated disposable income (taking into account public transfers to people), crime rate, and number of physicians. All the variables that are commonly used to assess socio-economic status that affect populations health [9,[47][48][49][50][51][52] are also related to the society-wide effect of income inequality described by Leigh et al 2009 [24]. In addition to these other possible mediators, we controlled the population density, which has also been reported to affect the population health.…”
Section: Other Variables Relating To Socioeconomic and Materials Condimentioning
confidence: 99%
See 1 more Smart Citation
“…These variables are aggregated disposable income (taking into account public transfers to people), crime rate, and number of physicians. All the variables that are commonly used to assess socio-economic status that affect populations health [9,[47][48][49][50][51][52] are also related to the society-wide effect of income inequality described by Leigh et al 2009 [24]. In addition to these other possible mediators, we controlled the population density, which has also been reported to affect the population health.…”
Section: Other Variables Relating To Socioeconomic and Materials Condimentioning
confidence: 99%
“…In the first stage, we tested whether these two variables would vary with income inequality. We performed this test by controlling for the average disposable income and the criminality rate, which may affect stress or depression [49,51,52,69,70].…”
Section: Analyzing Stress and Depression As Mediating Factorsmentioning
confidence: 99%
“…Kagee and Lund (2012) found that graduate training programmes in clinical psychology and counselling psychology had differing positions towards ESTs in clinical and counselling psychology. Kaminer and Eagle (2017) found that there are several EST's available to use by clinicians from LMICs. Yet the use of ESTs would be devoid of contextual considerations in the absence of locally conducted research.…”
Section: Implementation Of Pe In Lmicsmentioning
confidence: 99%
“…There is a gap in the knowledge of counselors and counselors in training regarding empirically supported interventions for treatment for child trauma (Kaminer & Eagle, 2016; Schneider et al, 2013). To address this gap, I featured TF-CBT and the intervention derivations as “important new therapies that show promise” (Schneider et al, 2013, p. 334).…”
Section: Trauma-focused Family Therapymentioning
confidence: 99%